2017
DOI: 10.1007/s00270-017-1657-6
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Electroporation to Treat Malignant Tumor Recurrences Within the Pelvic Cavity: A Case Series

Abstract: ObjectiveTo describe the initial experience with irreversible electroporation (IRE) to treat pelvic tumor recurrences.MethodsA retrospective single-center analysis was performed. Adverse events were recorded using Common Terminology Criteria of Adverse Events (CTCAE) 4.0. Clinical outcome was determined using pain- and general- symptom assessment, including Seddon’s peripheral nerve injury (PNI) types. Radiological outcome was evaluated by comparing baseline with three-month 18F-FDG PET-CT follow-up.ResultsEig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…This review found IRE to be safe for use in SRMs; as it was not associated with any mortalities, there were few 15 6 Good -Diehl et al 16 5 Good Fair Vroomen et al 17 1 Fair Poor Canvasser et al 18 41 Good Fair Liu et al 19 5 Fair Fair Wendler et al 20 7 Good Good Wendler et al 21 As above Good -Buijs et al 22 10 Good -Gul et al 23 1 Fair Fair clinically significant adverse events, and negligible effects on renal function. The two most observed adverse effects were transient haematuria and asymptomatic peri-renal haematomas.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…This review found IRE to be safe for use in SRMs; as it was not associated with any mortalities, there were few 15 6 Good -Diehl et al 16 5 Good Fair Vroomen et al 17 1 Fair Poor Canvasser et al 18 41 Good Fair Liu et al 19 5 Fair Fair Wendler et al 20 7 Good Good Wendler et al 21 As above Good -Buijs et al 22 10 Good -Gul et al 23 1 Fair Fair clinically significant adverse events, and negligible effects on renal function. The two most observed adverse effects were transient haematuria and asymptomatic peri-renal haematomas.…”
Section: Discussionmentioning
confidence: 86%
“…The full study designs of the included studies and the patient characteristics within the studies can be found in Tables 1 and 2. [14][15][16][17][18][19][20][21][22][23] Overall NOQAT Evaluation Scores were assigned to each article (Table 3). Generally, articles performed better at reporting safety and efficacy, as 6/10 were scored as good, however only 1/7 studies reporting on oncological outcomes was deemed to be of good quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations